(untitled) (Bangladesh Heart Journal, 2018)
Background : Diabetes mellitus is one of the important risk factors for coronary artery disease. The hemoglobin A1c is used for evaluating glycemic control in diabetic patients. Here, we conducted the study to evaluate the relationship between HbA1c level and severity of coronary artery disease among the hospitalized patients with ACS. Materials & Methods : This cross sectional study was conducted in the department of Cardiology, Ibrahim Cardiac Hospital & Research Institute, Dhaka, Bangladesh from September 2015 to December 2015. Total of one hundred patients were studied and they were grouped on the basis of their glycaemic status. One hundred patients with acute coronary syndrome were enrolled in this study. Out of them fifty were diabetic (HbA1c>6.5%) and rest of were nondiabetics (HbA1c<6.5%) ( group-A and B). Results: Out of one hundred patients fifty eight were male and fourty two were female. Mean age of patients in group-A was 58.54±10.22 years and mean age of patients in group-B was 54.52±13.69 years. Mean age of male and female was 57.72±11.48 years and 54.0±13.08 years respectively. Mean HbA1c of patients in group-A was 11.43±1.43% and group-B was 6.34±0.915%. 38% of group-A and 22% of group-B had triple vessel disease, 26% of group-A and 20% of group- B had double vessel disease and 28% of group-A and 18% of group-B had single vessel disease, and 8% of group-A and 40% of group-B had normal coronary arteries. 48% patients of age group 46-50 in group-A had more incidence in coronary artery disease than other age group which was statistically significant ( p=0.035). 61-75 years age group in group-B patients had coronary artery disease than other age groups which was statistically not significant(p=0.084). Patients of group-A was significantly relation with coronary artery disease (p>.001) and six times greater coronary artery disease than patients of group-B (OR= 6.15, 95% CI for OR =2.074 -18.289). Conclusions: In this way the importance of appropriate glycaemic control has been emphasized in diabetic patients. This study showed the relation between HbA1c levels and the severity of CAD in patient with type-II diabetes mellitus .Our findings demonstrate that elevated HbA1c level was risk factor for severity of coronary artery disease in ACS patients. Bangladesh Heart Journal 2018; 33(2) : 80-84